The Teachers’ Acceptance of Technology in a Remote English Teaching at SMA Negeri 4 Singaraja - Kadek Wira Arya Dharma (Journal of Educational Study, 2021)
This study is aimed to describe the English teachers’ acceptance of technology in remote English teaching. SMA Negeri 4 Singaraja is one of the senior high school that implementing remote English remote English teaching during the pandemic. Furthermore, in order to find out the English teachers’ acceptance in remote English teaching in SMA Negeri 4 Singaraja, Technology Acceptance Model (TAM) theory is used. The samples of this study were the 7 English of SMA Negeri 4 Singaraja. In order to collect the data, questionnaire was used. The data was collected from survey which was analyzed quantitatively. The result of this study showed that English teachers’ acceptance of technology in remote English teaching at SMA Negeri 4 Singaraja was neutral, which means they were either accepting remote English teaching or denying remote English teaching. However, their neutral acceptance was considered more to positive because several factors such as perceive ease of use and perceive of usefulness.